Measuring potential output at the Bank of Canada: The extended multivariate filter and the integrated framework - Lise Pichette; Pierre St-Amant; Ben Tomlin; Karine Anoma (Bank of Canada, 2015)
Estimating potential output and the output gap - the difference between actual output and its potential - is important for the proper conduct of monetary policy. However, the measurement and interpretation of potential output, and hence the output gap, is fraught with uncertainty, since it is unobservable. It is therefore important that we continually expand and improve upon existing models, and innovate by testing new approaches and incorporating them into the analysis of potential output and the output gap. Within this context, this paper first provides an assessment of the extended multivariate filter (EMVF), which the Bank has used since the late 1990s to come up with a baseline measure of the output gap. It is determined that the EMVF has several limitations that need to be addressed. Consequently, a modified version of the EMVF incorporating revised conditioning information is presented. In addition, a newly developed methodology, the integrated framework (IF), provides a separate analysis of trend labour input and trend labour productivity, and in doing so accounts for more long-term structural changes in the economy. While neither of these approaches is perfect, and both have limitations, they represent improvements over the conventional method. The paper also outlines how the modified EMVF, the IF, and information from the Bank's Business Outlook Survey and other sources are used to come up with an estimate of the current output gap and the future growth rate of potential output. – – L'estimation de la production potentielle et de l'écart de production – soit la différence entre la production effective et potentielle – est importante pour la conduite appropriée de la politique monétaire. Cependant, la production potentielle n'étant pas observable, la mesure et l'interprétation de cette variable, et par conséquent de l'écart de production, sont entourées d'incertitude. Il est donc essentiel de continuellement développer et améliorer les modèles existants, d'innover en mettant à l'essai de nouvelles méthodes et d'incorporer celles-ci dans l'analyse de la production potentielle et de l'écart de production. C'est dans cette optique qu'est d'abord proposée une évaluation du filtre multivarié élargi (EMVF) dont la Banque se sert depuis la fin des années 1990 pour établir une mesure de référence de l'écart de production. Ce filtre comporte plusieurs lacunes qu'il faut combler. Par conséquent, une version modifiée du filtre multivarié élargi comprenant une révision de l'information exploitée pour estimer la production potentielle est exposée. De plus, une méthode nouvelle procure une analyse distincte de la croissance tendancielle du facteur travail et de la croissance tendancielle de la productivité du travail, et prend en compte certains changements structurels à long terme de l'économie. Même si aucune de ces approches n'est parfaite, et bien qu'elles présentent toutes les deux des lacunes, elles constituent un progrès par rapport à la méthode de mesure habituelle de l'écart de production. L'étude décrit aussi de quelle manière le filtre élargi, le cadre intégré et l'information de l'enquête sur les perspectives des entreprises menée par la Banque sont utilisés avec d'autres sources pour estimer l'écart de production actuel et le taux de croissance future de la production potentielle.
Keywords: E0; E31; E5; E52; 330; Economic models; Inflation and prices; Labour markets; Productivity; Modèles économiques; Inflation et prix; Marchés du travail; Productivité